2006
DOI: 10.1300/j082v51n02_05
|View full text |Cite
|
Sign up to set email alerts
|

Positive Associations Among Interpersonal Contact, Motivation, and Implicit and Explicit Attitudes Toward Gay Men

Abstract: A correlational study explored the role of intergroup contact and motivation to respond without prejudice on heterosexuals' expression of explicit and implicit (unconscious) bias against gay men. Participants who reported having more relationships and closer relationships with gay, lesbian, or bisexual people tended to exhibit more favorable attitudes toward gay men on implicit as well as explicit attitude measures. Attitudes were also related to self-reported motivation to be non-prejudiced, including motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 30 publications
6
61
0
Order By: Relevance
“…Some recent studies (e.g., Lemm, 2006;Rohner & Björklund, 2006) have examined the relationship between implicit and explicit homonegativity. Further research is required to demonstrate the validity of these measures of homonegativity in comparison to traditional measures.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies (e.g., Lemm, 2006;Rohner & Björklund, 2006) have examined the relationship between implicit and explicit homonegativity. Further research is required to demonstrate the validity of these measures of homonegativity in comparison to traditional measures.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review uncovering more than 90 studies revealed that extended contact has widespread effects spanning across several outcome variables, target-groups, contexts and age-groups, thus supporting its role as an effective strategy to reduce prejudice (Vezzali, Hewstone, Capozza, Giovannini, & Wölfer, 2014). Notably, both direct (Fingerhut, 2012;Heinze & Horn, 2009;Lemm, 2006;West & Hewstone, 2012) and extended (Capozza, Falvo, Trifiletti, & Pagani, 2014;Hodson, Harry, & Mitchell, 2009;Mereish & Poteat, in press;Sharp, Voci, & Hewstone, 2011) contact have been shown to be effective means to improve attitudes towards homosexuals. However, none of these prior studies on intergroup contact has tested moral purity as a mediator of the effects of contact with sexual minorities despite the centrality of moral purity concerns in shaping attitudes towards homosexuals (Cottrell & Neuberg, 2005;Dasgupta et al, 2009;Inbar et al, 2009Inbar et al, , 2012.…”
Section: Direct and Extended Intergroup Contactmentioning
confidence: 99%
“…Indeed, individuals who are friends with or have had contact with sexual minorities tend to have more positive attitudes about members of that community (Heinze & Horn, 2009;Herek & Glunt, 1993;Hinrichs & Rosenberg, 2002;Lemm, 2006;Swank & Raiz, 2010). However, contact does not shape individuals' attitudes about sexual minorities in the same way.…”
Section: Conceptual Frameworkmentioning
confidence: 99%